Educational Values in Fasting Worship - Moch. Salman Alfarizi; Abdul Haris (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
The educational aspects contained in fasting are health education and moral education. This research aims to dig deeper into the educational values ​​contained in fasting in Islam. This research uses the library research research method, using a descriptive-analytical approach with a literature review type. The results of this research include that fasting teaches us important values ​​in life, including courage, discipline and empathy towards others. Perseverance and patience are also an integral part of fasting